Understanding the U.S. wars in Iraq and Afghanistan - Bailey, Beth L.; Immerman, Richard H. (New York University Press, 2015)
Understanding the U.S. Wars in Iraq and Afghanistan gives us the first book-length, expert historical analysis of these wars. It examines the lessons and legacies of wars whose outcomes may not be clear for decades.